(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Hanging is a form of asphyxia death due to constriction of the air passage at the neck, as a result of suspen sion of the body by a ligature in the form of a noose, applied in such a manner, when weight of the body or other part of the body e.g. head, acts as a constricting force. The present study has been done to describe the macroscopic changes which occur in the Hyoid Bone, Thyroid Cartilage and Common Carotid Artery in cases of Hanging. Methodology: The present study is an institution based observational study done during 1 year period from 1st April 2012 to 31st March 2013 and included 91 deceased selected by purposive sampling. Any unnatural deaths of both males and females of all age groups due to Hanging were included in the study, while asphyxial deaths other than due to Hanging or those with any anatomical anomaly or those in decomposed condition were excluded. Results and Discussion: Out of total 91 cases, most of hanging deaths were between 21- 30 years of age (27.5%). Only 4 had fractures of Hyoid bone each one belonged to the age group: 51-60 years, 61-70 years, 71-80 years and 81-90 years. Conclusion: This study was based only on macroscopical findings. If microscopical study is carried out on Common Carotid artery, which is beyond the limit of the present study, many more tears of the intima of the same artery could have been detected which was not identified in this study.